2013
DOI: 10.1155/2013/860514
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis Viruses in Heamodialysis Patients: An Added Insult to Injury?

Abstract: Hepatitis B (HBV) and hepatitis C (HCV) viruses are the most important causes of chronic liver disease in patients with end stage renal disease on hemodialysis. The prevalence of hepatitis infection among hemodialysis patients is high and varies between countries and between dialysis units within a single country. This case-control study was undertaken to estimate the occurrence of HBV and HCV infections in patients undergoing hemodialysis in our tertiary care center. All patients receving hemodialysis at our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
2
4
1
Order By: Relevance
“…This may be due to sample size, the method of detection and screening blood for antibodies against HCV with control measures in hospitals. Double infection with two viruses (HBV and HCV) in the same patient were not detected in our study while in other studies were 4.4% [ 26 , 27 ]. The lower number of the patients who were positive for anti- HCV after one year of follow-up was due to their deaths.…”
Section: Discussioncontrasting
confidence: 71%
“…This may be due to sample size, the method of detection and screening blood for antibodies against HCV with control measures in hospitals. Double infection with two viruses (HBV and HCV) in the same patient were not detected in our study while in other studies were 4.4% [ 26 , 27 ]. The lower number of the patients who were positive for anti- HCV after one year of follow-up was due to their deaths.…”
Section: Discussioncontrasting
confidence: 71%
“…A recent study by Kosaraju et al highlights the duration of dialysis as an important risk factor for infection among haemodialysis patients. 17 This observation was in agreement with previous reports in Palestine, Moldavia, and other studies from different regions of the world. [20][21][22][23] Duration of dialysis is an important risk factor for acquiring infections as it is related to nosocomial transmission and dissemination of the infections in the dialysis units.…”
Section: Discussionsupporting
confidence: 93%
“…In a recent study conducted by Kumar et al seroconversion rates for hepatitis C have been reported as 7.44% where as a high seroconversion rate of 14.4 % was reported in a study conducted by Mittal et al 12,13 Kosaraju et al in their study reported a very low prevalence and seroconversion rate of hepatitis B and C. 17 Similarly, we also found a low seroconversion rate of hepatitis C (4.8%) at our dialysis centre.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…(4) In addition, hemodialysis patients are usually anemic, need blood transfusion and invasive procedures more than the general population which also put them at higher risk of being infected with these viruses. (5) Therefore, patients undergoing hemodialysis are expected to have the highest rates of hepatitis B virus and hepatitis C virus infections and this is exactly what has been confirmed by the great majority of epidemiological studies which showed prevalence of hepatitis B and hepatitis C infections in hemodialysis units ranges from 1-20% and 1-55% respectively. (6,(15)(16)(17)(18) The presence of hepatitis B virus and/or hepatitis C virus in patients with chronic kidney disease can also increase the morbidity and mortality in these patients.…”
Section: Introductionmentioning
confidence: 72%